Technostress Level of Medical Education Study Program Students and Its Relationship With Sleep Quality - Ul-haq, Muhammad Mikail Zia; Noor, Zulkhah (International Journal of Health and Information System, 2025)
The prevalence of poor sleep quality among medical students is high, with some meeting the criteria for insomnia. This study aimed to examine differences in technostress levels based on gender, age, and year of study, as well as the relationship between technostress and sleep quality. Using an observational analytic design with a cross-sectional approach, 138 male and female students aged 17–23 years from three study years participated. Data were collected online using the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality and the Tech-Q questionnaire to measure technostress. Statistical analysis was conducted using Spearman's correlation test. Results indicated that female students experienced significantly higher technostress levels than males (p=0.002). However, technostress was not influenced by age, year of study, or associated with sleep quality (p>0.05). In conclusion, while gender differences in technostress exist, there is no correlation between technostress and sleep quality among medical students.